Organizational identity and firm growth : properties of growth, contextual identities and micro-level processes - Dörrenbächer, Christoph, 1961-; Dörrenbächer, Christoph, 1961-; Tomenendal, Matthias; Tomenendal, Matthias; Stanske, Sarah; Stanske, Sarah (Palgrave Macmillan, 2017)
This volume focuses on the interplay between organizational identities and firm growth and seeks to integrate psychological aspects to the discourse, thereby considering the micro, meso and macro level of the issue. - Resumé vydavatel
Keywords: identita organizace; management; ekonomický růst; corporate identity; economic development; elektronické knihy; kolektivní monografie; electronic books; collective monographs